Ranching through the Seasons in the Flint Hills - Jim Hoy (Symphony in the Flint Hills, 2012)
As anyone who has ever operated a farm or ranch knows, work never ends. Routine chores have to be done every day, while other jobs are seasonal, following a more or less predictable timetable. Over the years the methods of performing some ranch work in the Flint Hills has changed and some hasn’t, although the essence of that work is constant, dictated by the demands of caring for the land and livestock. Those demands themselves are controlled by the seasons.
Keywords: ranching; cattle; cows; summer; spring; fall; winter; autumn; seasons; hard work; farming; famer; steer; calves; cowboy; rancher; Flint Hills; Native Americans; Indians; Kansa; Kanza; reservation; fire; shipping; feedlots; burning; pasture; grassland; prairie